2016
DOI: 10.1128/aem.01510-16
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus rhamnosus Reduces Organophosphate Pesticide Absorption and Toxicity to Drosophila melanogaster

Abstract: Organophosphate pesticides used in agriculture can pose health risks to humans and wildlife. We hypothesized that dietary supplementation with Lactobacillus, a genus of commensal bacteria, would reduce absorption and toxicity of consumed organophosphate pesticides (parathion and chlorpyrifos [CP]). Several Lactobacillus species were screened for toleration of 100 ppm of CP or parathion in MRS broth based on 24-h growth curves. Certain Lactobacillus strains were unable to reach stationary-phase culture maxima a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 51 publications
2
61
0
7
Order By: Relevance
“…Findings from model systems support this approach, showing that Lactobacillus plantarum Lp39 can improve the innate immune response and resistance towards opportunistic infection in Drosophila melanogaster [19]. A reduction of pesticide toxicity via Lactobacillus rhamnosus GR-1 supplementation in D. melanogaster [20] and protection against harmful microorganisms by various Lactobacillus and Bifidobacterium spp. [21][22][23][24] has also been reported, suggesting these beneficial bacterial may be useful for directly addressing some of the causal factors implicated in honey bee decline.…”
Section: Introductionmentioning
confidence: 88%
“…Findings from model systems support this approach, showing that Lactobacillus plantarum Lp39 can improve the innate immune response and resistance towards opportunistic infection in Drosophila melanogaster [19]. A reduction of pesticide toxicity via Lactobacillus rhamnosus GR-1 supplementation in D. melanogaster [20] and protection against harmful microorganisms by various Lactobacillus and Bifidobacterium spp. [21][22][23][24] has also been reported, suggesting these beneficial bacterial may be useful for directly addressing some of the causal factors implicated in honey bee decline.…”
Section: Introductionmentioning
confidence: 88%
“…An appropriate assessment of the risk associated with these reported pathogens should, however, be carefully considered, as cell counts and/or the frequency of their presence would indicate if they really are of concern in these foods. Judging from numerous studies and reviews that have shown that fermentation and LABs are capable of reducing/degrading toxins and contaminants in foods [147,150,151,153,[172][173][174][175][176], it could be postulated that the levels found could either be 'residues' and or 'left-overs' of the fermentation process. The role of post contamination of these products should also not be ruled out as a possible source of these opportunistic microorganisms.…”
Section: Safety Of African Sorghum Fermented Foodsmentioning
confidence: 99%
“…Furthermore, Lactobacilli have shown potentials to sequester and degrade environmental toxins. They could sequester, but not metabolize, organophosphate pesticides (parathion and chlorpyrifos) and this sequestration was associated with decreased intestinal absorption and insect toxicity in appropriate models (Trinder et al, 2016). This could also be the case for PA in our experiments and this potential ability deserves to be studied more in detail.…”
Section: Discussionmentioning
confidence: 62%